Postnatal probiotic supplementation can prevent and optimize treatment of childhood asthma and atopic disorders: A systematic review of randomized controlled trials - Uwaezuoke, Samuel N.; Ayuk, Adaeze C.; Eze, Joy N.; Odimegwu, Chioma L.; Ndiokwelu, Chibuzo O.; Eze, Ikenna C. (Frontiers in Pediatrics, 2022)
Background: Although several randomized controlled trials (RCTs) published over the past five years show that prenatal or postnatal probiotics may prevent or optimize the treatment of childhood asthma and atopic disorders, findings from the systematic reviews and meta-analyses of these studies appear inconsistent. More recent RCTs have focused on postnatal probiotics, and linked specific probiotic strains to better disease outcomes. Objective: This systematic review aimed to determine if postnatal probiotics are as effective as prenatal probiotics in preventing or treating childhood asthma and atopic disorders. Methods: We searched the PubMed, Medline, Google Scholar, and EMBASE databases for RCTs published within the past five years (from 2017 to 2022). We included only full-text RCTs on human subjects published in or translated into the English language. We retrieved relevant data items with a preconceived data-extraction form and assessed the methodological quality of the selected RCTs using the Cochrane Collaboration's tool for assessing the risk of bias in randomized trials. We qualitatively synthesized the retrieved data to determine any significant differences in study endpoints of the probiotic and placebo groups. Results: A total of 1,320 participants (688 and 632 in the probiotic and placebo groups) from six RCTs were investigated. One RCT showed that early Lactobacillus rhamnosus GG (LGG) led to a reduction in the cumulative incidence rate of asthma. Another study demonstrated that mixed strains of Lactobacillus paracasei and Lactobacillus fermentum could support clinical improvement in children with asthma while one trial reported a significant reduction in the frequency of asthma exacerbations using a mixture of Ligilactobacillus salivarius and Bifidobacterium breve. Three trials showed that a combination of LGG and Bifidobacterium animalis subsp lactis, Lactobacillus rhamnosus alone, and a probiotic mixture of Lactobacillus ŁOCK strains improved clinical outcomes in children with atopic dermatitis and cow-milk protein allergy. Conclusions: Postnatal strain-specific probiotics (in single or mixed forms) are beneficial in preventing and treating atopic dermatitis and other allergies. Similarly, specific strains are more effective in preventing asthma or improving asthma outcomes. We recommend more interventional studies to establish the most useful probiotic strain in these allergic diseases.